I have found a new way of painting here”: Finnish paintresses in central Italy between the Eigheenth and Nineteenth Centuries (Altre Modernità, 2023)
The article investigates the stay in Italy of a group of influential Finnish women painters between the 19th and 20th century. Residing in Florence at different times in their lives, the artists explored areas of the Tuscan hinterland and coast outside the more traditional tourist destinations, at a time when a renewed interest in Italy, its culture and above all its ancient medieval and Renaissance painting traditions was maturing in Finland. The painters’ stay in Italy is therefore marked by the study of the art of the past, the exercise of copying, and the exploration of the Tuscan countryside, reinterpreted through a register that prefers linguistic experimentalism deduced from the comparison with local but also contemporary French and German art to the more consolidated Pittoresco style. The results are paintings and drawings, preserved in most cases at major Finnish museum sites, executed in the wake of that Nordic vitalist sensibility at the basis of which is the adoration of Mediterranean beauty as well as faith in the return of Classicism to Western civilisation.
Keywords: Middle Italy; Finland; Tuscany; Finnish artists; Macchiaioli; Expressionism; Avant-gardes